Immune Characteristics of IgA Nephropathy With Minimal Change Disease - Li, Huixian; Lu, Wanhong; Li, Haiyun; Liu, Xiaoling; Zhang, Xue; Xie, Liyi; Lan, Ping; Yu, Xiaoyang; Dai, Yinjuan; Xie, Xinfang; Lv, Jicheng (Frontiers in Pharmacology, 2021)
Background: IgA nephropathy (IgAN) has a high degree of heterogeneity in clinical and pathological features. Among all subsets of IgAN, the pathogenesis of IgAN with minimal change disease (MCD-IgAN) remained controversial. Methods: We analyzed the clinical and pathological characteristics of MCD-IgAN patients in a retrospective cohort. Patients diagnosed with IgAN, excluding MCD-IgAN, were randomly selected as controls. Levels of plasma galactose-deficient IgA1 (GdIgA1), IgG autoantibodies against GdIgA1, GdIgA1 deposition in the glomerulus, and inflammatory reactivity of circulating poly-IgA1 complexes to cultured mesangial cells were evaluated. Results: Patients with MCD-IgAN had significantly higher levels of proteinuria and estimated glomerular filtration rate (eGFR), lower levels of albumin and urine blood cells, and milder histological lesions by a light microscope compared to IgAN patients, which bears a resemblance to MCD. Lower levels of GdIgA1 (3.41 ± 1.68 vs. 4.92 ± 2.30 μg/ml, p = 0.009) and IgG antiglycan autoantibodies (23.25 ± 22.59 vs. 76.58 ± 71.22 IU/ml, p < 0.001) were found in MCD-IgAN patients than those in IgAN controls. Meanwhile, weaker fluorescence intensities of both IgA and GdIgA1 were observed in the glomerulus of MCD-IgAN patients compared to those in IgAN patients. Furthermore, poly-IgA1 complexes from MCD-IgAN patients induced weaker inflammatory effects on cultured mesangial cells than those from IgAN patients in vitro. Conclusion: The results demonstrated that MCD-IgAN cases represent a dual glomerulopathy, namely, mild IgAN with superimposed MCD, which furthermore provides substantial evidence for the corticosteroids therapy in MCD-IgAN patients as the guidelines recommended.